适用于模具法加工的弧齿锥齿轮精确建模 - 张华; 张占立; 魏冰阳; 李天兴 (Jixie chuandong)
To build the accuracy three-dimensional model of spiral bevel gear is of great significance for spiral bevel gear machining with mold processing method,such as precision forging,injection molding,powder forming and so on.Setting up machining coordinates,machining parameter is designed with local synthesis,and the machining parameters are verified by using TCA /LTCA technology.With facing cutter cone equation,machining parameters,and tooth surface boundary conditions,the key data points on tooth surface are obtained.Using three-dimensional modeling software,tooth surface patches are created firstly,and then,three-dimensional model of spiral bevel gear is built.As an example,the above procedure is introduced with a pair of spiral bevel gear.